2017
DOI: 10.1007/s00414-017-1589-3
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular androgenic-anabolic steroid-related remodeling: an immunohistochemical study

Abstract: In conclusion, the study indicates that, in very young subjects with chronic hypoxia-related alterations of the heart, signs of a heart failure in the other organs and a history of AAS abuse, death can be ascribed to progressive heart failure due to the direct apoptotic cardiac and endothelial changes produced by AAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Subsequently, we reported reduced left ventricular ejection fractions and ventricular diastolic impairments in middle-aged long-term users of supraphysiologic-dose AAS (Baggish et al, 2010), effects that we and others confirmed in subsequent larger-scale studies (Angell et al, 2012;Luijkx et al, 2013;Baggish et al, 2017;Rasmussen et al, 2018a). Other groups also have reported finding right ventricular abnormalities (Angell et al, 2014;Alizade et al, 2016;Rasmussen et al, 2018a), apoptosisrelated fibrotic changes in the heart (Cecchi et al, 2017), increased systolic blood pressure and aortic stiffness (Rasmussen et al, 2018b), and a pro-coagulant state (Chang et al, 2018) in long-term supraphysiologic-dose AAS users. In an echocardiography study in male rabbits, 6 months of supraphysiologic nandrolone administration (SC, 4 or 10 mg/kg, twice/ week) was associated with impaired global myocardial performance in a dose-related manner (Vasilaki et al, 2016).…”
Section: Cardiovascular Abnormalities Associated With Supraphysiologisupporting
confidence: 78%
“…Subsequently, we reported reduced left ventricular ejection fractions and ventricular diastolic impairments in middle-aged long-term users of supraphysiologic-dose AAS (Baggish et al, 2010), effects that we and others confirmed in subsequent larger-scale studies (Angell et al, 2012;Luijkx et al, 2013;Baggish et al, 2017;Rasmussen et al, 2018a). Other groups also have reported finding right ventricular abnormalities (Angell et al, 2014;Alizade et al, 2016;Rasmussen et al, 2018a), apoptosisrelated fibrotic changes in the heart (Cecchi et al, 2017), increased systolic blood pressure and aortic stiffness (Rasmussen et al, 2018b), and a pro-coagulant state (Chang et al, 2018) in long-term supraphysiologic-dose AAS users. In an echocardiography study in male rabbits, 6 months of supraphysiologic nandrolone administration (SC, 4 or 10 mg/kg, twice/ week) was associated with impaired global myocardial performance in a dose-related manner (Vasilaki et al, 2016).…”
Section: Cardiovascular Abnormalities Associated With Supraphysiologisupporting
confidence: 78%
“…Also, Montisci et al found left ventricular hypertrophy in four autopsies and even an association with fibrosis, myocytolysis, and drug-induced eosinophilic myocarditis [29]. Cecchi et al discovered a direct apoptotic cardiac and endothelial change in the heart tissue of deceased patients with heart failure who had a history of AS abuse [30]. In 2003, Hartgens et al conducted two echocardiographic studies over a period of 8-16 weeks in 17 AS users and 15 non-users [31].…”
Section: Cardiomyopathy and Asmentioning
confidence: 99%
“…AAS is associated with myocardial apoptosis. [48] In an animal model, ventricular myocytes were isolated from adult male rabbits and treated in vitro for 20 h using different doses of STZ, Testosterone Enanthate (TE), and Testosterone (T) (0.1, 1, 10, and 100 μmol/L). These results showed, for the first time, that AASs induce significant myocardial apoptosis in a dose-dependent manner.…”
Section: Effects Of Aas On the Cardiovascular Systemmentioning
confidence: 99%